Título Superior De Música. Relación Entre La Motivación De Logro Musical Y Las Conductas Desadaptativas De Abandono En Estudiantes - Zarza-Alzugaray, Francisco Javier (European Scientific Journal, ESJ, 2018)
The motivation of musical achievement is one of the main requirements to achieve academic success during the formative period of the students (Zarza, 2014). In this sense, behaviors such as the consumption of substances or cognitions such as thoughts of dropping out of musical studies are usually very present in music students and generate long-term maladaptive behavior sustained over time that can prevent a correct musical training or even the actual abandonment of them. We present a first approach to the relationship between motivation and substance use, as well as the presence of thoughts of abandonment. In this sense, an improvement is proposed in the training plans that tend to a greater individualization and surveillance of the presence of this type of behavior linked with low motivational levels.